Tracking wildebeest, locating knowledge: Maasai and conservation biology understandings of wildebeest behavior in northern Tanzania - Goldman, M. (SAGE Publications, 2007)
In this paper I argue for building dialogues between scientific and Maasai knowledge articulations, utilizing knowledge of wildebeest as an example. By locating Maasai and scientific knowledges regarding a particular subject (wildebeest) in relation to each other-in discourse and in practice-my intention is to create the space for their active engagement. I strive to (1) expose the situatedness, strengths, and weaknesses of both Maasai knowledge and scientific knowledge, and (2) illustrate the conditions within which collaborative dialogues can be constructed between the situated knowledges or knowledge spaces embodied by Maasai and conservation scientists. In doing so I hope to contribute to a shift in theoretical debates regarding knowledge integration for natural-resource management, away from 'building bridges' and towards the building of dialogues